Mendeteksi Pemahaman Konsep Perkalian Mahasiswa Calon Guru Madrasah Ibtidaiyah Melalui Problem Posing - Marhayati, Marhayati; Huda, Nuril (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This study aims to determine the understanding of the mathematical multiplication concept of Islamic Elementary School prospective teachers. This study applied a descriptive qualitative method. The research subjects were 33 students of Islamic Elementary Teacher Education Department at the Islamic State University of Maulana Malik Ibrahim Malang. Submission of mathematics questions is the learning strategy used in the Pembelajaran Matematika course. The results of data analysis showed that there were three categories: (1) understanding the concept of multiplication (33.3%); (2) understanding the concept of pseudo multiplication (18.2%); (3) not understanding the concept of multiplication (48.5%).